Enhanced physicochemical and functional properties of collagen films cross-linked with laccase oxidized phenolic acids for active edible food packaging. (1st November 2022) - Tang, Pingping; Zheng, Tingting; Yang, Changkai; Li, Guoying
Highlights: Hydroxybenzoic and hydroxycinnamic acids with different phenolic hydroxyl number were oxidized by laccase. More quinones formed with the increased phenolic hydroxyl number of phenolic acids. Physicochemical and functional properties of collagen film were enhanced owing to quinone-induced covalent cross-linking. Properties of collagen film were improved with the increased hydroxyl number of phenolic acids presumably because of more quinones formation caused by more hydroxyl groups. Abstract: Five different phenolic acids were oxidized by laccase. The UV–vis and FTIR results of oxidized phenolic acids indicated the formation of quinones and the amount of quinones enhanced with the increased phenolic hydroxyl number of phenolic acids. Then the quinones were used to modify collagen film. The FTIR and X-ray photoelectron spectra indicated that covalent cross-linking had formed between the quinones and the –NH2 of collagen molecules. Collagen films after being cross-linked with the quinones exhibited better physicochemical properties including water vapor permeability, resistance to enzyme degradation, mechanical property and thermostability. And these properties were significantly improved with the increased phenolic hydroxyl number of phenolic acids. Besides, the introduction of the phenolic acids endowed collagen film good antioxidant and antibacterial capacities. These results indicated that collagen film cross-linked by laccase oxidized phenolic acids showed potential for application as active edible food packaging.